Touch lib - Amno, Hasniza; Kasim, Mohd Jamil; Hashim, Siti Fatimah; Salis@Saleh, Md Naim; Shaharuddin, Bakiah (Universiti Teknologi MARA, Kedah, 2018)
Manual records and documentation of library attendance are regular methods practised by many libraries including the library of Institut Perubatan dan Pergigian Termaju (IPPT), USM. The manual method of using hard copies has many disadvantages due to loss of records, damaged, consuming space for long term storage, and lacks analytical tool. Realizing the problems, we opt for an automated attendance system which is essential to monitor the attendance of library users. A newlydevised online system was developed by using VB6 programming language and PHP to track records and monitors library users. The system was implemented in May 2018. This system was selected due to its simplicity and cost-effectiveness. The system named as “Touch Lib” functions as a tracking system that logs the number of admitted users in the Library. A computer and a card reader were utilized to develop and perform the system's operation. This system is in connection with the tapping of the identification card to the Library Automation System that is KOHA and HRMS (Human Resource Management System). It records the date and time registered users entered and left the library. The system collects the attendance of the library users, store the data and produce an analysis, which can be used as a valuable base point for the library‟s future planning such as physical and human resource management, and designing for library programs. Novelty and uniqueness: 1. In house development, it is a simple log-in/log-out program for monitoring user attendance. 2. A runtime program that was developed using VB6 and PHP and will run on Windows. 3. The system using an open source database knows as “MySQL” which is unlimited record keeping. 4. The system more flexible and customizable, require no extra costs and unique. 5. The system is a more accurate and quicker method of recording and monitoring user attendance. 6. A convenient way to recognize all registered or unregistered members as requirements before entering the library. 7. Statistics may be produced and accessible via online and kept in the organization server. 8. Functioning by wireless or wired network.